Understanding Customer Experience and Satisfaction in Luxury Hotels and Resorts: A Systematic Literature Review - Yafie Jasmi Azis, Muhammad; Mulia Wibawa, Berto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Objective: This study aims to systematically review and synthesize the existing literature on customer experience (CX) and customer satisfaction in the luxury hospitality sector, with a focus on luxury hotels and resorts. Specifically, it seeks to categorize how CX and satisfaction are conceptualized, identify key antecedents and dimensions, and summarize their outcomes on loyalty, recommendation behavior, and brand perception. Design/Methods/Approach: A Systematic Literature Review (SLR) was conducted using the Scopus database as the primary source. The search applied predefined inclusion and exclusion criteria, limiting results to peer-reviewed journal articles in English within the fields of business, management, and social sciences. A total of 50 articles published between 2015 and 2025 were selected. Following PRISMA procedures, thematic coding and synthesis were employed to map conceptual frameworks, methodological approaches, antecedents, and outcomes of CX and satisfaction in luxury hospitality. Findings: The review reveals that CX and satisfaction are multidimensional constructs encompassing sensory– aesthetic, emotional–relational, functional–hygiene, digital–technological, and sustainability dimensions. Key antecedents include servicescape design, staff interactions, brand authenticity, technology adoption, and ethical practices. Outcomes extend beyond behavioral loyalty to attitudinal loyalty, brand love, advocacy, and customer citizenship behaviors, with several studies identifying “indirect loyalty,” where satisfied guests recommend without revisiting. Theories frequently employed include the Experience Economy, SERVQUAL, Self-Congruity, Technology Acceptance Model, and Justice Theory. Originality/Value: This review contributes by integrating emerging dimensions such as sustainability and digital touchpoints into CX frameworks, highlighting the role of emotional–relational mediators, and reframing hygiene and functional quality as competitive assets in post-pandemic luxury hospitality. Practical/Policy implication: Findings suggest that managers should curate multisensory servicescapes, invest in staff cultural competence, balance AI-driven innovation with human interaction, and embed sustainable practices as intrinsic to luxury service. Policymakers can use these insights to shape guidelines that align luxury hospitality growth with sustainability goals